Observer design using a partial nonlinear observer canonical form - Röbenack, Klaus; Lynch, Alan F. (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes two methods for nonlinear observer design which are based on a partial nonlinear observer canonical form (POCF). Observability and integrability existence conditions for the new POCF are weaker than the well-established nonlinear observer canonical form (OCF), which achieves exact error linearization.
Keywords: observer design; canonical form; detectability